Tough Love: Impact of High-Performance Work System on Employee Innovation Behavior - Zhu, Fuyun; Gao, Ying; Chen, Xiaotun (Frontiers in Psychology, 2022)
Based on the social exchange theory, this paper discusses the impact of high-performance work system (HPWS) on employee innovation behavior, constructs the mediating model of challenge stress and the moderated mediation model, and explores the influence mechanism of HPWS on employee innovation behavior under the management mode of combining strictness and love formed by “strictness” under the effect of challenge stress and “love” given by perceived organizational support. Through hierarchical regression analysis of 227 employees’ survey data, the results show that HPWS positively influences employee innovation behavior. Challenge stress partially mediates the above relationship, and perceived organizational support positively moderates the mediating effect of challenge stress between HPWS and employee innovation behavior.